Clinical Management of Infectious Bovine Keratoconjunctivitis (IBK) With Ceftriaxone Sodium: A Case Report - Farg Alhadi Aboashia; Fatma Alatrag (African Journal of Advanced Pure and Applied Sciences, 2024)
Infectious bovine keratoconjunctivitis (IBK) is one of the most common eye diseases of cattle with a major economic impact in the world. This disease mainly caused by Moraxella bovis (M. bovis) bacteria. This bacterial infection of the eye causes inflammation which may lead to temporary or permanent blindness. Many types of local and systemic antibiotics and anti-inflammatory agents were used in treating the condition. This paper presents the case of infectious bovine keratoconjunctivitis in a four months pregnant lactating Holstein Friesian cow aged 5 years old, 300Kg weighing was presented to the clinic with primary complains of eye problem and inappetence and loss of appetite since five days. Clinical examination findings revealed that the cow was depressed. The most prominent abnormality observed was corneal opacity of the right eye with presence of chemosis of the right conjunctiva with excessive lacrimation. The cow was treated with Intramuscular injection of Ceftrimax (5mg/ kg b.wt) five doses in alternative days. Phenylbutazon (4mg/ kg b.wt) was given intramuscularly once daily for three days as anti-inflammatory and analgesic. Furthermore, Genta-Dex eye drop (Gentamycin and Dexamethasone) was applied twice daily for 2 days. Conclusion: The prognosis for this case was good as the cow was treated promptly and effectively by Ceftriaxone sodium intramuscularly.